Conformity assessment analysis of self-declare ecolabel criteria for Indonesia’s tourism villages development in Cikolelet, Banten Province - Andi Dewi Sartika Syamsul; Ita Lestari; Sukma Arini; Dissa Natria; Toto Iswanto; Budi utomo (Politeknik Negeri Bali, 2023)
This study aimed to observe the potential of conformity ecolabel self-declaration claims in Cikolelet Tourism Village, Banten Province, Indonesia. The village has an alternative tourism highland nature, unique culture, creative industry, and environmental conservation. Local people and tourism activities impacted the quality of the village, especially waste management. The literature review and field observation were applied to assess the Self Declare Ecolabel Criteria for waste management in Cikolelet using applicable standards and regulations in Indonesia. The scope of waste management applied to the tourism village includes compostable, recyclable, reusable, and waste reduction. According to the result of assessment and observations, generally, Cikolelet Tourism Village has made environmental management efforts. However, some lack of waste management in terms of waste reduction and handling, including sorting, transportation, processing, and final disposal, requires some improvements to comply with environmentally friendly criteria. A strong commitment is required to actualize the scope of the ecolabel self-declaration.